A PREVENTIVE APPLICATION IMPROVIZED USING ARID PLANT DERIVATES: NOSOCOMIAL PREVENTIVE REMEDY - Kaushik, Itishree; Datta, Manali (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Epidermis acts as a niche for plethora of infection causing bacteria. It is a necessity to maintain the microbial populations in acceptable levels to attain hygienic conditions. In this study, an attempt has been made to prepare and test the functioning of antimicrobial cloth using desert plant extracts. Methods: Comparative antibacterial and radical scavenging activity of the aqueous and methanolic extracts from plants namely Saccharum spontaneum, Prosopsis cineria and Balanites aegyptica was tested. Minimum inhibitory concentration (MIC) against Staphylococcus aureus MTCC 7443, Streptococcus pneumonia MTCC 655, Escherichia coli NCIM 2642, Pseudomonas aeroginosa MTCC 8295, Bacillus megaterium NCIM 2326, Bacillus subtilis NCIM 2329 ranged from 20 µg to 50 µg for the various extracts utilized. DNAse activity was also checked for the extracts to estimate the potency of extract for skin damage. Results: Based on the MIC ranges, an excess amount (100 µg) of the extract was loaded on the cotton cloth and check for antimicrobial potential. DNAse activity was also checked for the extracts to estimate the potency of extract for skin damage. No extract tested was found to have DNA degradation activity. Conclusion: Based on the manifested results, cotton cloth loaded with 100 µg/cm of crude extracts from Balanites aegyptica may be successfully used as an antimicrobial cloth. Fabrics capable of sterilization would have potential benefits to reduce disease transfers among hospital populations and bio‑warfare protection. Keywords: Balanites aegyptica, Antimicrobial, Cotton cloth, Desert plant extract, Skin microflora. 2